Chromosomal breaks mediated by bile acid-induced apoptosis in nasopharyngeal epithelial cells : in relation to matrix association region/scaffold attachment region. - Tan, Sang Nee; Sim, Sai Peng (2016)
Introduction: Chronic rhinosinusitis (CRS) has been recognised as a risk factor for nasopharyngeal carcinoma (NPC). CRS can be triggered by gastroesophageal reflux (GER) that may reach the nasopharynx. Bile acid (BA), the main component of refluxate, is a potential carcinogen. BA-induced apoptosis has been implicated in various malignancies. Chromosomal breakage is an early event in both apoptosis and chromosomal rearrangement. Matrix Attachment Region/Scaffold Attachment Region (MAR/SAR) appears to be a preferential site of chromosomal breakage. We hypothesised that BA-induced apoptosis may cause chromosomal breaks at MAR/SAR leading to NPC chromosomal rearrangements.